Uptake and Accumulation of Mineral Elements from Winery and Distillery Effluents by Typha latifolia and Phragmites australis - Zingelwa, N.S.; Wooldridge, J. (South African Journal of Enology and Viticulture, 2016)
Mineral element uptake by the macrophytes Typha latifolia (bulrush) and Phragmites australis (common reed) from effluent (waste water) was investigated in a two-year sampling program carried out in constructed wetlands at a winery near Stellenbosch (33°55’S, 18°52’E), and at a distillery near Worcester (33°32’S, 19°13’E) in the Western Cape Province. Factors considered were: season of growth, site (distillery or winery), plant kind, wetland retention time and position in the wetland (inflow, outflow). Effluent nitrogen (N), potassium (K), calcium (Ca), magnesium (Mg) and sodium (Na) concentrations were lower at the outflow than at the inflow at the winery, but not the distillery. Dry mass increases in both macrophytes were greater at the distillery than the winery. The distillery effluent contained higher concentrations of N and K than that from the winery. Tissue N, P, K, Na, Ca, Mg, copper (Cu) and zinc (Zn) concentrations were higher in plants at the distillery than at the winery. Tissue N and K concentrations were, respectively, higher and lower in P. australis than in T. latifolia. Retention time, and position within the wetland, had either no, or inconsistent, effects on tissue element concentrations. The total element contents of the macrophytes were small in relation to the quantities of elements in the effluent. Where differences in effluent composition across the winery wetland were observed, these were probably due to biological activity in the effluent itself, on the limestone gravel surfaces, or on the plant roots.